Relaxin-3/RXFP3 Signaling and Neuroendocrine Function – A Perspective on Extrinsic Hypothalamic Control - Ganella, Despina E.; Ma, Sherie; Gundlach, Andrew L. (Frontiers in Endocrinology, 2013)
Complex neural circuits within the hypothalamus that govern essential autonomic processes and associated behaviors signal using amino acid and monoamine transmitters and a variety of neuropeptide (hormone) modulators, often via G-protein coupled receptors (GPCRs) and associated cellular pathways. Relaxin-3 is a recently identified neuropeptide that is highly conserved throughout evolution. Neurons expressing relaxin-3 are located in the brainstem, but broadly innervate the entire limbic system including the hypothalamus. Extensive anatomical data in rodents and non-human primate, and recent regulatory and functional data, suggest relaxin-3 signaling via its cognate GPCR, RXFP3, has a broad range of effects on neuroendocrine function associated with stress responses, feeding and metabolism, motivation and reward, and possibly sexual behavior and reproduction. Therefore, this article aims to highlight the growing appreciation of the relaxin-3/RXFP3 system as an important ‘extrinsic’ regulator of the neuroendocrine axis by reviewing its neuroanatomy and its putative roles in arousal-, stress- and feeding-related behaviors and links to associated neural substrates and signaling networks. Current evidence identifies RXFP3 as a potential therapeutic target for treatment of neuroendocrine disorders and related behavioral dysfunction.